The TGF-?-inducible miR-23a cluster attenuates IFN-? levels and antigen-specific cytotoxicity in human CD8? T cells - Chandran, P. Anoop; Keller, Andreas; Weinmann, Lasse; Seida, Ahmed Adel; Braun, Matthias; Andreev, Katerina; Fischer, Birgitt; Horn, Evi; Schwinn, Stefanie; Junker, Markus; Houben, Roland; Dombrowski, Yvonne; et al. (Journal of Leukocyte Biology, 2014)
Cytokine secretion and degranulation represent key components of CD8(+) T-cell cytotoxicity. While transcriptional blockade of IFN-? and inhibition of degranulation by TGF-? are well established, we wondered whether TGF-? could also induce immune-regulatory miRNAs in human CD8(+) T cells. We used miRNA microarrays and high-throughput sequencing in combination with qRT-PCR and found that TGF-? promotes expression of the miR-23a cluster in human CD8(+) T cells. Likewise, TGF-? up-regulated expression of the cluster in CD8(+) T cells from wild-type mice, but not in cells from mice with tissue-specific expression of a dominant-negative TGF-? type II receptor. Reporter gene assays including site mutations confirmed that miR-23a specifically targets the 3'UTR of CD107a/LAMP1 mRNA, whereas the further miRNAs expressed in this cluster-namely, miR-27a and -24-target the 3'UTR of IFN-? mRNA. Upon modulation of the miR-23a cluster by the respective miRNA antagomirs and mimics, we observed significant changes in IFN-? expression, but only slight effects on CD107a/LAMP1 expression. Still, overexpression of the cluster attenuated the cytotoxic activity of antigen-specific CD8(+) T cells. These functional data thus reveal that the miR-23a cluster not only is induced by TGF-?, but also exerts a suppressive effect on CD8(+) T-cell effector functions, even in the absence of TGF-? signaling.
EVALuna2:25970